Dynamic Analyses of the Short‐Term Effects of Different Bisphosphonates Using Intravital Two‐Photon Microscopy. (22nd June 2018) - Kikuta, Junichi; Shirazaki, Mai; Sudo, Takao; Mizuno, Hiroki; Morimoto, Akito; Suehara, Riko; Minoshima, Masafumi; Kikuchi, Kazuya; Ishii, Masaru
ABSTRACT: Bisphosphonates are commonly used for the treatment of bone disorders such as osteoporosis; however, the mechanism by which they affect the dynamics of living mature osteoclasts in vivo remains unknown. Here, we describe the short‐term effects of different bisphosphonates on controlling the bone resorptive activity of mature osteoclasts in living bone tissues of mice using intravital two‐photon microscopy with a pH‐sensing chemical fluorescent probe. Three types of nitrogen‐containing bisphosphonates, risedronate, alendronate, and minodronate, inhibited osteoclastic acidification during osteoporotic conditions just 12 hours after i.v. injection. Among the three types of drugs, risedronate was the most effective at increasing osteoclast motility and changing the localization of proton pumps, which led to an inhibition of bone resorption. Together, these results demonstrate that the intravital imaging system is a useful tool for evaluating the similarities and differences in currently used antibone resorptive drugs. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.